The Effects of Zinc Oxide (ZnO) Quantum Dots (QDs) Embedment on the Physicochemical Properties and Photocatalytic Activity of Titanium Dioxide (TiO2) Nanoparticles - Iqbal, Anwar; Usman, Saidu; Adam, Farook; Sreekantan, Srimala; Jasni, Normawati; Ahmad, Mohammad Norazmi (Universiti Sains Malaysia, 2021)
In this study, a detailed investigation on the effect of zinc oxide (ZnO) quantum dots (QDs) embedment on the physicochemical properties of anatase titanium dioxide (TiO2) was conducted. The highly porous nanocomposite labelled as ZQT was prepared via the sol-gel assisted hydrothermal method. The powder X-ray diffraction (XRD) analysis indicates that the average crystallite size of the ZnO QDs, anatase TiO2 (TiO2 NPs) and ZQT were 4.45 nm, 9.22 nm and 11.38 nm, respectively. Photoluminescent (PL) analysis detected the presence of defects related to TiO2, oxygen vacancies and quantum confinement effect (QCE) of the ZnO QDs in ZQT. These features enhanced the photodegradation of tetracycline (TC) under 48 watt of fluorescent light irradiation when ZQT (98.0%) was used compared to TiO2 NPs (32.4%) and ZnO QDs (68.8%). The photodegradation activity was driven by O2 ●− followed by ●OH and h+.